2013
DOI: 10.1097/01.mxe.0000430775.91633.7f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in-vitro protective effect of plant extract (astaxanthin) on chromosomal breakage in Fanconi anemia cell culture

Abstract: BackgroundFanconi anemia (FA) is an inherited bone marrow failure syndrome associated with congenital abnormalities and hypersensitivity to DNA cross-linking agents. The high frequency of chromosomal breaks in FA lymphocytes has been related to the increased oxidative damage shown by these cells. Reactive oxygen species (ROS) are derived from the metabolism of molecular oxygen. It is now assumed that ROS are involved both in the initiation and in the progression of cancer. Antioxidants have the ability to tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Also, Resveratrol affected the cultures of normal control group to reduce their average levels from 5 / 1000 studied cells in untreated cultures to zero in treated cultures. This effect of Resveratrol could be compared to other antioxidants as Astaxanthinbioactive natural carotenoidwhich decreases the level of induction of breakage by DEB in FA patients (Capelli and Cysewski, 2007;Eid et al, 2013). In this study it was found that the Resveratrol has effect on correction of genomic damage, this encourage the application of the in vitro test on large number of patient's samples with different concentrations of…”
Section: Resultsmentioning
confidence: 51%
“…Also, Resveratrol affected the cultures of normal control group to reduce their average levels from 5 / 1000 studied cells in untreated cultures to zero in treated cultures. This effect of Resveratrol could be compared to other antioxidants as Astaxanthinbioactive natural carotenoidwhich decreases the level of induction of breakage by DEB in FA patients (Capelli and Cysewski, 2007;Eid et al, 2013). In this study it was found that the Resveratrol has effect on correction of genomic damage, this encourage the application of the in vitro test on large number of patient's samples with different concentrations of…”
Section: Resultsmentioning
confidence: 51%